Development of Learning Media Using Livewire Application and Printed Circuit Board Wizard in Electronic Circuit Application Subject - Dewi, Diana; Widayatsih, Tri; Putra, Muhammad Juliansyah (Journal of Social Work and Science Education, 2024)
This study aims to develop an interactive module using Livewire and PCB Wizard applications to facilitate students in designing electronic circuits in the subject of electronic circuit applications. The study employed the methods of analysis, design, development, implementation, and evaluation (ADDIE). Furthermore, there was an improvement in scores from the experimental class compared to the control class. Expert evaluations resulted in an average score of 4,24 with a percentage of 84,93%. The effectiveness questionnaire from students yielded a score of 4,53 with a percentage of 90,07%. These findings indicate that the interactive video is considered effective and practical for use, demonstrating that the use of Livewire and PCB Wizard applications can significantly improve students’ abilities in designing electronic circuits.